Penggunaan Multimedia Untuk Meningkatkan Motivasi Belajar Siswa - Nur Habibah, Kholimatus Sa'diyah; Murtopo, Bahrun Ali; Maesaroh, Maesaroh (IBTIDA-Jurnal Kajian Pendidikan Dasar, 2022)
This study aims to analyze the use of multimedia to improve the learning motivation of students at Madrasah Tsanawiyah. The approach used is qualitative. The subjects are three students and three teachers and the location chosen to be the research site is MTs Negeri 1 Kebumen. Data collection techniques include observation, interviews and documentation. Data analysis techniques are through data reduction activities, data presentation and verification or drawing conclusions. Based on the results of the study, students' learning motivation can increase when learning Islamic Religious Education, especially in the subjects of faith, morals and fiqh when using multimedia in the learning process. This can be seen from the enthusiasm of students during teaching and learning activities in the classroom, the focus of students is much higher, namely after paying attention to the teacher's explanation, the desire of students to note new things that are considered very important and easy to understand or understand the learning material that has been studied.